Evidence-based national suicide prevention taskforce in Europe: A consensus position paper - Zalsman, G; Hawton, K; Wasserman, D; van Heeringen, K; Arensman, E; Sarchiapone, M; Carli, V; Höschl, C; Winkler, P; Balazs, J; Purebl, G; Kahn, J; et al. (Elsevier, 2017)
More than 150,000 in Europe and 800,000 people worldwide, die every year by suicide (WHO, 2015), accounting for 1·4% of all annual deaths. Suicide is the second, and in some European countries even the first leading cause of death amongst young people aged 15-24 years (WHO, 2015), thus exceeding the number of accidental deaths. The European parliament resolution on Mental Health 2008/2209 (INI) adopted a series of recommendations for European member states. It proposed areas for priority action as defined in the European Pact on Mental Health and Well-Being. Recently, 29 suicide prevention experts from 17 European countries (The Task Force for the European Evidence-Based Suicide Prevention Program, EESPP) performed a systematic review of evidence for the effectiveness of suicide prevention interventions that has been published over the last decade. During three face-to-face meetings, the EESPP group developed a consensus declaration that, based on the findings of the systematic reviews, summarizes the minimal requirements for a national suicide prevention programs and of the strategies to employ.